Renewable energy benefits : leveraging local capacity for offshore wind (International Renewable Energy Agency, 2018)
Offshore wind projects create ample opportunities for local value creation. Income and jobs can be maximised by leveraging existing economic activities and building upon domestic supply chains. Education and training, however, must be attuned to emerging needs in the offshore wind industry. The development of a typical 500-megawatt offshore wind farm requires around 2.1 million person-days of work. Manufacturing takes up 59% of the labour requirements of such a project, followed by operation and maintenance (24%) and installation and grid connection (11%). Factory workers account for more than half of the labour needed in manufacturing. Offshore wind development benefits from synergies with offshore oil and gas, specifically in terms of skills and occupational patterns. Successful job migration between sectors, however, depends on dedicated retraining policies. Specific policy measures, such as upgrading and supplier development programmes, support for joint ventures, or industrial promotion schemes, may be needed to strengthen the industrial capacity of domestic firms.
Keywords: Wind power -- Economic aspects.; Ocean energy resources.; Renewable energy sources.; elektronické knihy; electronic books